Compliance of Teaching Material Components with Educational Standards - Maslani Maslani; Salma Nadhifa; Hikma Nurfadila; Rizal Nurzain (Jurnal Iman dan Spiritualitas, 2026)
This study aims to assess the suitability of teaching material components to national education standards through a literature review approach. Teaching materials are a crucial instrument in the learning process, serving not only as a medium for delivering content but also as a bridge between the curriculum and classroom practice. However, in the field, teaching materials are still found to be not fully structured according to national standards, both in terms of content, delivery strategies, and evaluation. Through a literature analysis, this study found that the ideal structure of teaching materials includes components such as learning objectives, materials, learning activities, evaluation, media, and character values, all of which must be arranged coherently and contextually. Recommended approaches to teaching material development include scientific, competency-based, differentiation, and Universal Design for Learning (UDL). In addition, the use of digital technologies such as Learning Management Systems (LMS) and interactive multimedia also enriches the components of teaching materials to make them more adaptive and engaging. This study also identified real challenges in teaching material development, including limited teacher training, inadequate facilities, and low digital literacy. Therefore, strategies are recommended to enhance teacher competency, foster collaboration among educators, facilitate continuous evaluation, and strengthen support from the government and educational institutions. These findings are expected to serve as a reference for teachers, curriculum developers, and policymakers in creating quality teaching materials that are relevant to today's learning dynamics.